SPECTRAL REFLECTANCE PROPERTIES OF SOIL TAXONOMY UNITS DOMINANT IN SAQLAWIYAH PROJECT - & Al-Obaidy, Al-Juraysi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The area under study is located at the lower of resent Mesopotamian plain of Euphrates river, located between longitude 43 35 to 43 35 East and latitude 33 22 to 33 27 North with area (3445.38 ha.) at 169 path and 37 row of Landsat-5 taken by Thematic Mapper image sensor (TM). The space images taken during the year 1985, were used ERDAS V.8.2 and GIS V.9.2 Software. using data of soil survey report.A study show ability of Spectral reflectance to detecting the Aridisols and Entisols and can be also detecting sub- great group at Typic Haplogypsids and Typic Haplosalids taxonomy units appeared to be distinguished and isolated. While there were difficult to detecting and identification between Vertic Torrifluvents and Typic Torrifluvents.